Impact of elevated pCO2 on benthic foraminiferafrom the southwestern Baltic Sea - Haynert, Kristin (2013)
Increasing atmospheric CO2 concentrations have a strong impact on the marine carbonate chemistry leading to a phenomenon called ocean acidification. Excess CO2 dissolves in the surface water of the ocean, thereby the seawater pCO2 increases, whereas the [CO3 2-] and pH decrease. Reduced CO3 2- concentrations may affect marine, especially calcifying, organisms such as benthic foraminifera, in that their ability to form calcareous tests might be affected. In comparison to open oceans, water pCO2 levels are often not in equilibrium with the atmosphere in coastal regions, which are characterized by high CO2 variability during the seasonal cycle. This has also been observed for the southwestern Baltic, an eutrophic marginal sea, where bacterial degradation of large amounts of organic matter cause O2 depletion and CO2 enrichment in the bottom water. In the frame of this thesis, the impact of elevated pCO2, temperature and salinity changes on the survival and calcification ability of the benthic foraminiferal species Ammonia aomoriensis was investigated in mid-term and long-term laboratory experiments. Under laboratory conditions, foraminifera were either isolated from the sediment or remained in their natural microhabitat. Further, the natural carbonate system variability and its impact on foraminiferal communities were monitored in a one-year field study. Specimens of Ammonia aomoriensis were isolated from their natural sediment. They exhibited reduced survival and growth rates with increasing pCO2 of up to 3130 μatm under laboratory conditions. At pCO2 levels above 1800 μatm, dissolution caused a decrease of test diameter, and at the highest pCO2, only the inner organic lining remained. Testing the combined effects of ocean acidification, temperature and salinity on living Ammonia aomoriensis, a significant reduction of test diameter was observed at a pCO2 >1200 μatm (Ωcalc<1). Tests were mainly affected by undersaturation of calcite. This effect was partly compensated by a temperature rise, which increased ...